The Influence of Motivation and Work Environment on Employee Performance in Food and Beverage Service Hotel Granmelia Jakarta - Ardi Mularsari*; Selena Aura Prameswari (Riwayat: Educational Journal of History and Humanities, 2023)
The purpose of this study was to analyze the effect of motivation and work environment on employee performance in food and beverage service at Hotel Granmelia Jakarta. By using quantitative methods. In this study, the data collection method used questionnaires as many as 25 samples to 25 food and beverage service employees at Hotel Granmelia Jakarta. Research data analysis using SPSS 23 with research testing methods including Validity Test, Reliability Test, Classical Assumption Test and Multiple Linear Regression Test. The results showed that motivation had a positive and significant effect on employee performance, and the work environment had a positive and significant effect on employee performance.